The Effect of Unemployment Insurance on Temporary Help Services Employment. - Edisis, Adrienne (Journal of Labor Research, 2016)
A model with fixed effects and controls for state-specific linear time trends is developed to analyze the influence of state unemployment insurance taxes on temporary help services employment using state level panel data from the Bureau of Labor Statistics' Quarterly Census of Employment and Wages. Prior research has shown that imperfect experience rating of unemployment insurance taxes increases temporary layoffs and that, conversely, more extensive experience rating leads to a decrease in temporary layoffs. The current analysis demonstrates that more extensive experience rating increases temporary help services agency-intermediated temporary employment. To the extent that the increase in temporary help services employment represents a substitution of temporary help services jobs for traditional direct hire jobs, it implies a negative effect on job quality. Steps to address low unemployment insurance recipiency rates by temporary help services workers may alleviate the impact of unemployment insurance tax structures on temporary help services employment.